2021
DOI: 10.12998/wjcc.v9.i24.7169
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic basal ganglia calcification associated with new MYORG mutation site: A case report

Abstract: BACKGROUND Idiopathic basal ganglia calcification (IBGC) is a neurodegenerative disease characterized by symmetrical calcification of basal ganglia and other brain region, also known as Fahr’s disease. It can be sporadic or familial, and there is no definite etiology at present. With the development of neuroimaging, the number of reports of IBGC has increased in recent years. However, due to its hidden onset, diverse clinical manifestations, and low incidence, it is likely to be misdiagnosed or ig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…We searched through PubMed until April 1, 2023 for relevant studies and scanned the reference lists in the identified articles. We reviewed all reported cases of PFBC with biallelic MYORG mutations and summarized all the mutation sites in Table 1 (Arkadir et al, 2019 ; Chelban et al, 2020 ; Chen, Lin, et al, 2020 ; Chen, Cen, et al, 2020 ; Chen et al, 2019 ; Fei et al, 2021 ; Ferreira & de Oliveira, 2019 ; Forouhideh et al, 2019 ; Gao et al, 2022 ; Grangeon et al, 2019 ; Kume et al, 2020 ; Li et al, 2022 ; Liu et al, 2021 ; Malaquias et al, 2020 ; Peng et al, 2018 ; Ramos et al, 2019 ; Sadok et al, 2023 ; Saranza et al, 2020 ; Taglia et al, 2019 ; Tekin et al, 2021 ; Tsai et al, 2022 ; Yang et al, 2022 ; Yao et al, 2018 ; Zeng et al, 2021 ). Data for 62 families have been reported, 51% of the patients were men and 49% were women.…”
Section: Resultsmentioning
confidence: 99%
“…We searched through PubMed until April 1, 2023 for relevant studies and scanned the reference lists in the identified articles. We reviewed all reported cases of PFBC with biallelic MYORG mutations and summarized all the mutation sites in Table 1 (Arkadir et al, 2019 ; Chelban et al, 2020 ; Chen, Lin, et al, 2020 ; Chen, Cen, et al, 2020 ; Chen et al, 2019 ; Fei et al, 2021 ; Ferreira & de Oliveira, 2019 ; Forouhideh et al, 2019 ; Gao et al, 2022 ; Grangeon et al, 2019 ; Kume et al, 2020 ; Li et al, 2022 ; Liu et al, 2021 ; Malaquias et al, 2020 ; Peng et al, 2018 ; Ramos et al, 2019 ; Sadok et al, 2023 ; Saranza et al, 2020 ; Taglia et al, 2019 ; Tekin et al, 2021 ; Tsai et al, 2022 ; Yang et al, 2022 ; Yao et al, 2018 ; Zeng et al, 2021 ). Data for 62 families have been reported, 51% of the patients were men and 49% were women.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we found that 9/42 of the mutations we summarized were loss-of-function (LOF) mutations, whereas 27/42 were missense mutations ( Figure 2A ). MYORG is specifically expressed in astrocytes, and may regulate protein glycosylation in the endoplasmic reticulum of brain astrocytes ( 8 , 13 , 15 ). Inactivation of the MYORG glycosidase function may lead to abnormal protein glycosylation and metabolism, which may lay the foundation for the formation of brain calcification ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…The missense change is the most common variant type in the MYORG gene, followed by in-frame indels, nonsense, and frameshift variations. There is no obvious hotspot of pathogenic variants ( Figure 1 e) [ 3 , 10 , 22 , 24 , 25 , 26 , 27 , 30 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 ]. Pathogenic variants cause the loss of the glycosidase function of MYORG , which may lead to abnormal protein glycosylation and metabolic disturbance.…”
Section: Genetics and Disease Mechanismmentioning
confidence: 99%